2006
DOI: 10.1080/10934520600966649
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Source Assessment of Heavy Metals and Polycyclic Aromatic Hydrocarbons (PAHs) in Sediments of the Fosu Lagoon, Ghana

Abstract: The first results ever obtained on polycyclic aromatic hydrocarbon (PAHs) concentrations in the Fosu lagoon surface sediments are presented together with corresponding heavy metal (Fe, Mn, Cd, Zn and Ni) concentrations. Samples collected on a monthly basis from November 2003-April 2004 (Heavy metals) and December 2003-January 2004 (PAHs) at 8 locations, representing different anthropogenic sources of contamination to the lagoon, were analyzed. Concentrations of Cd and Ni in the lagoon sediment suggest greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
2
20
1
Order By: Relevance
“…The lagoon is only about 50 m from the Gulf of Guinea. The Lagoon is surrounded by many sites that can act as point sources for discharge of pollutants (Gilbert et al 2006). These include: domestic waste discharges from a residential area in the northern side of the lagoon, industrial waste discharge from a mechanical workshop on the North Eastern side, drains from a college and a hospital on the Western and South Western side, and household dumping and effluents and sewage from the southern end.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lagoon is only about 50 m from the Gulf of Guinea. The Lagoon is surrounded by many sites that can act as point sources for discharge of pollutants (Gilbert et al 2006). These include: domestic waste discharges from a residential area in the northern side of the lagoon, industrial waste discharge from a mechanical workshop on the North Eastern side, drains from a college and a hospital on the Western and South Western side, and household dumping and effluents and sewage from the southern end.…”
Section: Methodsmentioning
confidence: 99%
“…These may probably be outdated and may not represent current pollution trends in the municipality. We had recently published the heavy metal and PAH levels in the sediment of the Fosu Lagoon (Gilbert et al 2006), and an assessment of heavy metal pollution of one other surface water in the municipality, Iture Estuary, was only recently reported in the course of writing this manuscript (Fianko et al 2007). Recent general water quality data in water sources in the municipality are still lacking in the literature.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The result for correlation analysis between individual PAHs in water from QIRE revealed that the in Surface Water in Lower Reach of Qua Iboe River Estuary, Nigeria compounds were derived from a common anthropogenic origin [27]. The strong positive correlation between B(k)F and chrysene observed in this study may be due to close relatedness in molecular weight [28].…”
Section: Resultsmentioning
confidence: 60%
“…The Fosu Lagoon is considered to be highly polluted (Armah et al 2010) due to the disposal of waste, water withdrawal for irrigation, reduction in size of the popular black chin tilapia in recent years, and increasing severity of algal blooms (Gilbert et al 2006, Darkwa andSmardon 2010). Discharge into the lagoon from a cluster of mechanical workshops a source of Iron (Fe), Magnesium (Mn), Cadmium (Cd), Zinc (Zn), and Nickel (Ni) in the Fosu Lagoon (Gilbert et al 2006). Though there is no industrialization around the Benya Lagoon, its proximity to a fish market, which serves about 500 individuals weekly, creates the likelihood of waste and effluent disposal through the associated anthropogenic activity.…”
Section: Introductionmentioning
confidence: 99%